Mengukur Kepuasan Nasabah: Etika Bisnis, Inovasi Produk dan Layanan Digital di BSI KCP Binjai - Kita Delvia Br Ginting; Elida Elfi Barus (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The banking industry is undergoing a massive transformation towards a digital ecosystem, requiring a strategic balance between technological advancement and ethical compliance. This research aims to analyze the influence of Islamic business ethics, product innovation, and digital services on customer satisfaction at Bank Syariah Indonesia (BSI) KCP Binjai. Using a quantitative approach, data were collected from 100 respondents through purposive sampling and analyzed using multiple linear regression. The results indicate that Islamic business ethics, product innovation, and digital services simultaneously and partially have a significant positive effect on customer satisfaction. Business ethics serves as the primary foundation for building emotional trust, while product innovation prevents customer saturation. Digital services, particularly through the Byond by BSI application, represent the most dominant factor in enhancing transactional efficiency. However, challenges remain regarding digital literacy and system stability during peak hours. This study suggests that BSI KCP Binjai should prioritize human resource development in ethical standards and strengthen its technological infrastructure to maintain long-term competitive advantages.